Topological Model of the Pseudogap State: Experimental Signatures - Diamantini, M. C.; Trugenberger, C. A.; Bollinger, A. T.; Vinokur, V. M.; Božović, I. (Frontiers in Physics, 2022)
We summarize the basic ideas of our topological model of the pseudogap state of high-temperature superconductors (HTS) as a condensate of charged magnetic monopoles, with a focus on new experimental signatures. These include the surface quantum Hall effect, the generation of electric fields when applying magnetic fields by the oblique Meissner effect, and the generation of circular electric fields surrounding electric currents by the oblique Ampère law.